DEVELOPMENT OF THE THINKING PROCESS IN PRESCHOOL CHILDREN - Bekmuradova Dilnoza Pirimovna (Journals Park Publishing, 2023)
The special role of preschool age in the further development of human development, the preparation of the child for school education The role of teaching preschool education conditioned the need for research. With this in mind, in this article we explored ways to develop the cognitive activity of preschool children.